2016
DOI: 10.1002/berj.3250
|View full text |Cite
|
Sign up to set email alerts
|

How does the choice of A‐level subjects vary with students' socio‐economic status in English state schools?

Abstract: The reasons why students from lower socio‐economic groups are under‐represented at high status universities are not yet entirely understood, but evidence suggests that part of the gap may be a consequence of differential choice of A‐levels by social background. The Russell Group of universities has since 2011 published guidance on A‐level subject choices, describing some A‐levels as ‘facilitating’ in that choosing these helps keep the largest number of Russell Group degree courses open. The numbers of students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…The existing literature shows that subject choice at age 16-18 matters for educational trajectories, income, and social mobility (for example Chevalier, 2011;Dilnot, 2016;Dolton & Vignoles, 2002). Previous research has found that there are large differentials in subject choice by social background at GCSE (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The existing literature shows that subject choice at age 16-18 matters for educational trajectories, income, and social mobility (for example Chevalier, 2011;Dilnot, 2016;Dolton & Vignoles, 2002). Previous research has found that there are large differentials in subject choice by social background at GCSE (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…and A-level (e.g. Dilnot, 2016). More specifically, young people from higher socioeconomic backgrounds (SES) are more likely to take facilitating subjects (see for example, Dilnot, 2016;Toth, Sammons, & Sylva, 2015;Vidal Rodeiro, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…But that still gives a wide variety of subjects from which students may choose, and these choices may make a difference to their chances of acceptance at university in general, and high-status university in particular. As discussed elsewhere in this issue, schools may constrain choices at age 14 (Anders, Henderson, Moulton, & Sullivan, 2018) which has a knock-on effect on A-level choices (Dilnot, 2016). Most students applying to university do so during Year 13 with grades predicted by their schools in each of their A-levels, and offers of places from universities are made in terms of both the A-level subjects being followed and the required grade to be obtained.…”
Section: Introductionmentioning
confidence: 99%